Chemico-genetic discovery of astrocytic control of inhibition in vivo - Takano, Tetsuya; Wallace, John T.; Baldwin, Katherine T.; Purkey, Alicia M.; Uezu, Akiyoshi; Courtland, Jamie L.; Soderblom, Erik J.; Shimogori, Tomomi; Maness, Patricia F.; Eroglu, Cagla; Soderling, Scott H. (Nature (London), 2020)
Perisynaptic astrocytic processes are an integral part of central nervous system synapses 1 , 2 ; however, the molecular mechanisms that govern astrocyte–synapse adhesions and how astrocyte contacts control synapse formation and function are largely unknown. Here we use an in vivo chemico-genetic approach that applies a cell-surface fragment complementation strategy, Split-TurboID, and identify a proteome that is enriched at astrocyte–neuron junctions in vivo, which includes neuronal cell adhesion molecule (NRCAM). We find that NRCAM is expressed in cortical astrocytes, localizes to perisynaptic contacts and is required to restrict neuropil infiltration by astrocytic processes. Furthermore, we show that astrocytic NRCAM interacts transcellularly with neuronal NRCAM coupled to gephyrin at inhibitory postsynapses. Depletion of astrocytic NRCAM reduces numbers of inhibitory synapses without altering glutamatergic synaptic density. Moreover, loss of astrocytic NRCAM markedly decreases inhibitory synaptic function, with minor effects on excitation. Thus, our results present a proteomic framework for how astrocytes interface with neurons and reveal how astrocytes control GABAergic synapse formation and function. A cell-surface fragment complementation strategy is used to identify the proteome at the junction of astrocytes and synapses in vivo, and shows that NRCAM expressed in astrocytes has a key role in regulating inhibitory synapse function.